2019
DOI: 10.1002/ccd.28628
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of percutaneous intervention for pulmonary vein stenosis after pulmonary vein isolation procedure

Abstract: Objectives Report long‐term outcomes of percutaneous intervention in patients with pulmonary vein stenosis (PVS) after pulmonary vein isolation (PVI) from a single center over 16 years. Background Outcome reports of percutaneous intervention for PVS resulting from PVI are limited. Methods Retrospective review of all patients with PVS after PVI who underwent percutaneous intervention at the Cleveland Clinic Foundation between January 2000 and December 2016. Results A total of 205 patients underwent cardiac cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Whether using a stent or balloon dilation, the diameter of the device is reported to be an important factor in longterm patency. 21,29 Our cohort data also showed a trend towards lower restenosis rates in patients with devices ≥7 mm in diameter and in patients with a BMS or DCB. However, it should be kept in mind that it is not clear whether this result is due to the choice of larger-diameter devices or BMS, or because originally larger vessels have a better outcome.…”
Section: Device Options and Long-term Restenosissupporting
confidence: 60%
“…Whether using a stent or balloon dilation, the diameter of the device is reported to be an important factor in longterm patency. 21,29 Our cohort data also showed a trend towards lower restenosis rates in patients with devices ≥7 mm in diameter and in patients with a BMS or DCB. However, it should be kept in mind that it is not clear whether this result is due to the choice of larger-diameter devices or BMS, or because originally larger vessels have a better outcome.…”
Section: Device Options and Long-term Restenosissupporting
confidence: 60%
“…[3] Larger stents appear to reduce the rate of reintervention compared with small stents and BA. [112] For restenosis, a reintervention with high-pressure ballooning, cutting balloon, and stent-in-stent is often needed. Procedure-related complications should also be considered.…”
Section: Catheter-based Interventionsmentioning
confidence: 99%
“…Procedure-related complications should also be considered. For PVI-PVS, in a single-center and retrospective study, Suntharos et al [112] have reviewed a total of 205 patients who underwent cardiac catheterization for PVS during 2000 to 2016 and reported overall complications of 9.5% and severe complications of 4.5%, including cardiac arrest, pulmonary vein tear, and stroke. Furthermore, Duan et al [55] have shown a high incidence of procedure-related lung injury (44%) in FM-PVS.…”
Section: Catheter-based Interventionsmentioning
confidence: 99%
“…PVS-FM is attributed to extraluminal proliferative fibrous tissue compression, [12] while other PVS are attributed to intimal hyperplasia. [13,14] Hence, even though PTPV has been successfully used in PVS-PVI, PTPV in PVS-FM might be different. Our preliminary data showed that patients with PVS-FM who underwent interventions, both in terms of hemodynamics and exercise capacity, had clinical improvement but a high prevalence of restenosis during a very short-term follow-up.…”
Section: Introductionmentioning
confidence: 99%